2006
DOI: 10.1093/toxsci/kfl055
|View full text |Cite
|
Sign up to set email alerts
|

The 2005 World Health Organization Reevaluation of Human and Mammalian Toxic Equivalency Factors for Dioxins and Dioxin-Like Compounds

Abstract: In June 2005, a World Health Organization (WHO)-International Programme on Chemical Safety expert meeting was held in Geneva during which the toxic equivalency factors (TEFs) for dioxin-like compounds, including some polychlorinated biphenyls (PCBs), were reevaluated. For this reevaluation process, the refined TEF database recently published by Haws et al. (2006, Toxicol. Sci. 89, 4-30) was used as a starting point. Decisions about a TEF value were made based on a combination of unweighted relative effect pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
1,939
4
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,241 publications
(1,995 citation statements)
references
References 125 publications
30
1,939
4
22
Order By: Relevance
“…PCB81 and PCB77 contributed the second greatest proportion It should be noted that the brominated analogues such as polybrominated diphenyl ethers (PBDEs) and polybrominated dibenzo-p-dioxins/furans (PBDD/Fs) have not been studied in this work. Though PBDEs, which were widely used as flame retardants in e-products, do not have AhR agonist properties by themselves, PBDD/Fs occur as trace contaminants in commercial PBDEs and can be produced during open burning of e-waste containing PBDEs (8). Both in vitro and in vivo studies have shown that PBDD/Fs are potent AhR agonists and cause dioxin-like effects (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCB81 and PCB77 contributed the second greatest proportion It should be noted that the brominated analogues such as polybrominated diphenyl ethers (PBDEs) and polybrominated dibenzo-p-dioxins/furans (PBDD/Fs) have not been studied in this work. Though PBDEs, which were widely used as flame retardants in e-products, do not have AhR agonist properties by themselves, PBDD/Fs occur as trace contaminants in commercial PBDEs and can be produced during open burning of e-waste containing PBDEs (8). Both in vitro and in vivo studies have shown that PBDD/Fs are potent AhR agonists and cause dioxin-like effects (8).…”
Section: Resultsmentioning
confidence: 99%
“…Though PBDEs, which were widely used as flame retardants in e-products, do not have AhR agonist properties by themselves, PBDD/Fs occur as trace contaminants in commercial PBDEs and can be produced during open burning of e-waste containing PBDEs (8). Both in vitro and in vivo studies have shown that PBDD/Fs are potent AhR agonists and cause dioxin-like effects (8). Therefore, these compounds should be further studied in the e-waste recycling area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of lethality may be ascribed to interspecific differences of PCB congeners on the activation of the AhR; according to these data, tree swallows have lower sensitivity to PCBs than other avian species [5,7,8,40]. Similarly, the potency of dioxin-like PCBs with similar chemical structures to dioxins (e.g., 2,3,7,8-tetrachlorodibenzodioxin) is toxicologically categorized by TEFs [41,42]. Thus PCB 77 (dioxin-like PCB congener), with a TEF of 0.0004 in kestrels (Falco sparverius), 0.005 in turkeys (Meleagris gallopavo), and 0.05 in chickens (Gallus gallus domesticus), should likely have significant adverse effects [6,14,43].…”
Section: Exposure To Pcb 77 Did Not Affect Survivabilitymentioning
confidence: 97%
“…For congeners with concentrations below the limit of detection (LOD), a value of half the LOD was used to calculate the total concentration and the TEQ. The WHO-TEF 2005 values reported by Van den Berg et al [18] were used to calculate the TEQs for the PCDD/Fs and dlPCBs. The TEQs for the dioxin like PCNs (dl-PCNs) and HxCBz were calculated based on the relative potency factors (RPFs) reported by Noma et al [19] and van Birgelen [20], respectively.…”
Section: Concentrations Of Unintentional Pops Emitted From Thermal Wimentioning
confidence: 99%